MicroRNAs as Indicators into the Causes and Consequences of Whole-Genome Duplication Events. (3rd December 2021) - Peterson, Kevin J; Beavan, Alan; Chabot, Peter J; McPeek, Mark A; Pisani, Davide; Fromm, Bastian; Simakov, Oleg
Abstract: Whole-genome duplications (WGDs) have long been considered the causal mechanism underlying dramatic increases to morphological complexity due to the neo-functionalization of paralogs generated during these events. Nonetheless, an alternative hypothesis suggests that behind the retention of most paralogs is not neo-functionalization, but instead the degree of the inter-connectivity of the intended gene product, as well as the mode of the WGD itself. Here, we explore both the causes and consequences of WGD by examining the distribution, expression, and molecular evolution of microRNAs (miRNAs) in both gnathostome vertebrates as well as chelicerate arthropods. We find that although the number of miRNA paralogs tracks the number of WGDs experienced within the lineage, few of these paralogs experienced changes to the seed sequence, and thus are functionally equivalent relative to their mRNA targets. Nonetheless, in gnathostomes, although the retention of paralogs following the 1R autotetraploidization event is similar across the two subgenomes, the paralogs generated by the gnathostome 2R allotetraploidization event are retained in higher numbers on one subgenome relative to the second, with the miRNAs found on the preferred subgenome showing both higher expression of mature miRNA transcripts and slower molecular evolution of the precursor miRNA sequences. Importantly, WGDs do not result in the creation of miRNA novelty, nor do WGDs correlate to increases in complexity. Instead, it is the number of miRNA seed sequences in the genome itself that not only better correlate to instances in complexification, but also mechanistically explain why complexity increases when new miRNA families are established.